Hepatitis B and C Infection in Gujrat, Pakistan: A Cross Sectional Study - Sajid Mehmood; Abdullah Mashori; Hira Khalid; Asim Mushtaq; Jagdesh; Muhammad Zeeshan Hyder (Journal of Bahria University Medical and Dental College, 2021)
Objective: This study was aimed to investigate the prevalence of Hep B and C, gender distribution, route of transmission, family history of Hepatitis and treatment options. Study Design and Setting: This was a cross sectional study conducted at Dr Mujahid's Lab Bhimber road Gujrat, Pakistan. Methodology: A total of 1181 individuals were included in this study. Among these 1181 individuals, 528 individuals were screened for hepatitis B and C by immuno chromatographic test (ICT) at Dr. Mujahid’s Lab, Bhimber road, Gujrat while rest of the 653 individuals were asked about the hepatitis status by using a well-structured questionnaire. Other related questions were also included like age, sex, marital status, mode of transmission, and about treatment to evaluate the risk factors associated with disease. Data was analyzed by using SPSS 17. Results: Prevalence of hepatitis B and C was 1.37% and 8.26% in surveyed while 1.5% and 9.1% in screened population of district Gujrat respectively. In surveyed hepatitis C patients, 72% were females and 28% were males. Among these, 91% patients were married and only 9% were unmarried. In case of hepatitis C, 9% stated polluted water, 9% medicines, 5.5% family history, 3.7% barber, 2% endemic, 2% dental surgery, 2% unhygienic food and 2% typhoid fever as a cause of infection while for hepatitis B, 33% individual’s stated low standard hoteling as a cause of infection. Overall, incidence of hepatitis was higher in screened individuals as compared to surveyed. Conclusion: This study concluded that hepatitis prevalence is high in district Gujarat. Moreover, Hepatitis C is more frequent than hepatitis B in this area.